Business process management : 18th International Conference, BPM 2020, Seville, Spain, September 13-18, 2020, Proceedings /: 18th International Conference, BPM 2020, Seville, Spain, September 13-18, 2020, Proceedings. (2020) - Unknown
No abstract available